Kontribusi Pemerintah Desa dalam Meningkatkan Pemberdayaan Karang Taruna - Andri, Andri; Isabella, Isabella; Amaliatulwalidain, Amaliatulwalidain (Jurnal Publisitas, 2023)
This study aims to find out how Contribution village government in increasing the empowerment of government youth organizations the village has a very influential role, especially in efforts to creating a climate that encourages the growth of community initiatives and self-help in rural areas which is carried out through development messages, guidance to the community to participate in development and distribution community aspirations. This qualitative research method can present data that is not monotonous, boring, and not fixated on one point, from theoretical indicators This will be used by researchers to develop so as to get the same results want to achieve later. The results of study indicate that this program assessed well by conducting in-depth interviews and making observations to these activities guided by the role indicators, namely: (1) Expectations, (2) Norms, (3) Forms of Behavior, (4) Assessment and Sanctions. This hope related to the desire for a behavior that will be obtained, of course this wish or hope is addressed to a figure who has a role. This norm is divided into two types, namely veiled expectations viz expectations that remain even if not spoken (such as obligations) and expectations which is open i.e. a wish that is uttered (a request or a demands). Behavioral manifestations in this role can be assumed to be evident or actions that have been taken by the village head in carrying out development for the youth organization in his village. Assessment and Sanctions based on these wishes or expectations will produce a good impression or bad. This point will be the assessment of the head's behavior the village so far against youth organizations.